Modelling the Determinants of Tax Compliance Behavior in Ghana: The Moderating Role of Attitude Towards Tax, and Tax Environment - Tefuttor, Christoph Kweku; Nsor-Ambala, Randolph; Onumah, Regina; Agbeibor, Juliet (International Journal of Economics and Financial Issues, 2026)
Ghana’s tax-to-GDP ratio approximately stands at 13.40%, which is well below the World Bank’s recommendation of 25% for sustainable economic growth. Tax systems play a crucial role in the development of the national economy with the provision of necessary revenues for the operations of government and the public services. Yet, the effectiveness of these systems is largely dependent on the compliance behaviour of the taxpayers. To address this challenge and enhance individuals’ tax compliance behaviour in fulfilling their tax obligations, this paper aimed to develop a robust model to explain the determinants of tax compliance behaviour by adopting the theory of planned behaviour with slight variation and the mediating role of attitude towards tax and tax environment. This study is built on the positivist paradigm, the quantitative research approach and the survey research design. The data was collected from a cross-section of Ghanaian small and medium enterprises in Ghana between August and December 2024. The structural equation modelling approach was used in analysing the survey data. The study has revealed that tax knowledge, awareness and perception of fairness are significant determinants of attitude towards tax. Moreover, there are mediating roles of attitude towards tax and the overall tax environment in shaping tax compliance behaviour. The implication of the results is that there is a need for tax authorities to prioritise educational programmes in enhancing tax knowledge and awareness among citizens. The newly developed model could be used to guide major stakeholders to ensure a sustainable, transparent and fair tax system in the emerging economy context.